2007
DOI: 10.1111/j.1365-2133.2007.08197.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcus aureus toxins and nasal carriage in furuncles and impetigo

Abstract: PVL is not involved in all types of furuncles but is associated with epidemic furunculosis. Both bullous and nonbullous forms of impetigo are associated with exfoliative toxins. Staphylococcus aureus nasal carriage is associated with the chronicity of furuncles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 46 publications
4
60
1
3
Order By: Relevance
“…In our cohort, 85% of MSSA isolates from patients with furunculosis harbored luk-PV genes. Others have reported luk-PV gene frequencies of from 30 to 97% among isolates causing SSTIs (10,18,21,31,39). In striking contrast, the prevalence of luk-PV among colonizing S. aureus strains was below 1%, which, again, is in agreement with the findings of previous studies (22,38).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our cohort, 85% of MSSA isolates from patients with furunculosis harbored luk-PV genes. Others have reported luk-PV gene frequencies of from 30 to 97% among isolates causing SSTIs (10,18,21,31,39). In striking contrast, the prevalence of luk-PV among colonizing S. aureus strains was below 1%, which, again, is in agreement with the findings of previous studies (22,38).…”
Section: Discussionsupporting
confidence: 83%
“…These strains commonly cause staphylococcal scalded skin syndrome and bullous impetigo (28,43), toxin-mediated staphylococcal diseases which are associated with eta or etb in 65 to 100% of the cases (10,18,26,30,60). One such CC121 clone, characterized by ST123 and spa type t171, is notorious as the "epidemic European fusidic acid-resistant impetigo clone (EEFIC)" (27-29, 42, 44, 52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the toxins, Panton-Valentine leukocidin (PVL) is associated with human pyogenic necrotizing skin infections such as furuncles, cellulitis, and abscesses, and more severe septic infections such as osteomyelitis, bacteremia, purpura fulminans, and necrotizing pneumonia (1)(2)(3)(4)(5)(6)(7)(8). PVL with γ-hemolysins (HlgA/HlgB and HlgC/ HlgB) and LukE/LukD belongs to the bicomponent pore-forming leukotoxin family (9)(10)(11)(12)(13)(14), which are thought to contribute to virulence in various infection models (15)(16)(17)(18), although some groups disagree (19,20).…”
mentioning
confidence: 99%
“…In three Czech strains of S. aureus, the presence of lukS-PV a lukF-PV genes were determined by the National Reference Laboratory in the year 2004 and found to belong to CA-MRSA 56 . Antimicrobial resistance tests and selected methods of molecular biology demonstrated that their characteristics diff er from the multi-drug resistant HA-MRSA strains described in hospital patients 14,39,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Current Knowledge Of Methicillin-resistant Staphylococcus Aumentioning
confidence: 99%